# Algebra2

posted by .

If f (x) = x² + 3 and g (x) = 3x - 1 then find the following:

1a. (f+g)(x)

1b. (f+g)(3)

1c. (f-g)(x)

1d. (fg)(x)

1e. (fg)(-1)

• Algebra2 -

1a. (f+g)(x) = f(x)+g(x) = x^2 + 3 + 3x - 1 = x^2 + 3x + 2

1b. (f+g)(3) = 9+3+2 = 14

1c. (f-g) = x^2 - 3x + 4

1d. (fg)(x) = f(x)*g(x) = (x^2+3)(3x-1) = 3x^3 - x^2 + 9x - 3

1e. (fg)(-1) = -3 - 1 - 9 - 3 = -16

## Similar Questions

1. ### Algebra2

find the value of the following expressions; 8! 12!
2. ### Algebra2

If f (x) = x² + 3 and g (x) = 3x - 1 then find the following: 1. (f/g)(x) 2. (f o g)(x) 3. (f o g)(1) 4. (g o f)(x)
3. ### algebra2

If f (x) = x² + 3 and g (x) = 3x - 1 then find the following: 1. (f/g)(x) 2. (f o g)(x) 3. (f o g)(1) 4. (g o f)(x)
4. ### Algebra2

HELP? f = (1, 2), (2, 3), (3, 4), (4, 5), g = (1, -2), (3, -3), (5, -5), and h = (1, 0), (2, 1), (3, 2), Find the following and state the domain?

find the asymptotes for the following inverse function(VA is X and HA isY) y=7/(x) -4 i get VA: x=0 ,and HA :-4

find the vertical asymptotes of the following rational function(remember VA is X) x+6/(x^2+11x+30 ) my answer is x+6/(x+6)(x+5) cancel alike term i get 1/(x+5 )and V.A:x=-5 is that right thanks